Post-Sekularisme Dan Tantangan Pastoral Gereja - Otto Gusti Madung (Jurnal Alternatif Wacana Ilmiah Interkultural, 2017)
Post-secularism was born in the form of the emergence of religions in the public sphere. It is the antithesis of the secularization view characterized by the marginalization of religion into the private sphere. The rise of religion in the public sphere features a double face. On the one hand it appears in the face of violence as it appears in various forms of religious fundamentalism and terrorism. On the other hand religion offers moral potentiality that can solve various ethical public issues such as euthanasia, abortion and the crisis of meaning facing modern society. For pastoral work the post-secular church offers a number of challenges and opportunities at once. Churches that appear in public spaces must deal with plural public sphere conditions. This requires the Church to translate its pre-political messages into interfaith language. In addition, the Church is also required to live up to tolerance as a virtue of democracy.